As linguagens em Pascal: carne, espírito e caridade - Thiago Borges de Almeida (2012)
This masters thesis aims to investigate the relationship, in Pascals work, between the doctrine of the three orders and the way the author uses words to write a Christian apologetic. To accomplish that, we have tried to extract from his writings a conception of language compatible with the foundations of Pascalian thought, foundations which we have established as being anthropology, questions relating to the method, and the doctrine of the three orders. Within this framework, we have postulated that Pascal's argument, as undertaken in his Pensées, unfolds on three levels: the language of the flesh, comprising the spheres of desire, the body, the "Machine", habit and imagination; the language of the spirit, which relates to the scientific method, deduction, Descartes and mathematics; and the language of charity, which always refers to the Bible, through the miracles, signs and figures.